Preparation and Properties of Polyurethane Films with Spent Coffee Grounds - Li, Rui Xue; Wang, Hao; Jiang, Shan; Xu, Wei Lin; Shen, Xiao Lin; Zhou, Yi (Materials science forum, 2016)
In this study, a method of recycling spent coffee grounds (SCG) is introduced. The SCG was dried and crushed into micron-sized coffee particles. The coffee particles could be used to prepared polyurethane (PU) films with different contents (0wt.%, 5wt.%, 10wt.%, 15wt.%, 20wt.%, 25wt.% and 30wt.%). The anti-ultraviolet property, thermal comfort performance and mechanical property of different PU films were measured. The results showed that after the blending of coffee particles, the films exhibited excellent anti-ultraviolet property and thermal comfort performance, and the mechanical properties were also retained. This study also provided an effective approach to reuse SCG, which is consistent with the environmental-friendly society principle.